Hematology patient reported symptom screen to assess quality of life for AL amyloidosis. Issue 5 (20th March 2017) - Warsame, Rahma; Kumar, Shaji K.; Gertz, Morie A.; Lacy, Martha Q.; Buadi, Francis K.; Hayman, Suzanne R.; Leung, Nelson; Dingli, David; Lust, John A.; Lin, Yi; Russell, Stephen; Kapoor, Prashant; et al.
Abstract: Patients with light chain amyloidosis (AL) often have delayed diagnosis and present with significant symptomatology; this may result in decreased quality of life (QOL). We prospectively employ a "Hematology Patient Reported Symptom Screen" (HPRSS), which is three questions about fatigue, pain, and QOL, scored 0–10. The aim of this study is to better understand QOL and determine if HPRSS parameters predict for clinical outcomes. From 2009 to 2014, 302 newly diagnosed AL patients were included. Baseline median scores [interquartile range] for fatigue, pain, and QOL were 6 [3, 7], 2 [0, 5], 5 [3, 8], respectively. Median overall survival was 53 months, with 102 (34%) deaths in the first year. There were significant differences in baseline HPRSS between those that lived longer than one year and early death patients in the domains of fatigue (5 [IQR 3, 7] vs. 7 [IQR 5, 8], P < 0.0001) and QOL (6 [IQR 4, 8] vs. 5 [IQR 3, 7], P = 0.006). On univariate analysis fatigue, QOL, physician‐reported performance status, autologous stem cell transplant (ASCT), and Mayo stage were prognostic for survival. On multivariate analysis Mayo stage, ASCT, and baseline fatigue remained independently prognostic. When analyses were restricted to the 125 patients with HPRSS measurements at 12 months, we found that over time QOL scores improved significantly 6 [IQR 3.5, 8] → 7 [IQR 5, 8] ( P = 0.01). Asking AL patients to rate their fatigue and QOL has predictive value. Baseline patient reported fatigue is an independent prognostic factor for survival. Survival at one year was associated with significant improvement in QOL.